Lnc-MAP6-1:3 knockdown inhibits osteosarcoma progression by modulating Bax/Bcl-2 and Wnt/β-catenin pathways - Lin, Hao (Int J Med Sci, 2020)
Osteosarcoma (OS) is the most common type of malignant bone tumor that affects children and adolescents. Still, the cellular and molecular mechanisms driving the development of this disease remain poorly understood. In this study, numerous dysregulated lncRNAs were identified by RNA-seq. As a result, we were able to find a novel lncRNA Lnc-MAP6-1:3 which is highly expressed in osteosarcoma. Using a set of approaches including gene knockdown, RT-PCR, oncogenic function assay and western blotting, we observed that knockdown of Lnc-MAP6-1:3 expression suppressed cell proliferation and colony formation, and promoted apoptosis in vitro. For the first time, we have identified that Lnc-MAP6-1:3 potentially influence the malignant behavior of osteosarcoma via Bax/Bcl-2 and Wnt/β-catenin signaling pathways. Henceforth, Lnc-MAP6-1:3 may provide a new molecular route of research and therapeutic applications for the diagnosis and treatment of osteosarcoma.